Language Change in the Communication of Generation Z - Marzona, Yessy (Jurnal Ilmiah Langue and Parole, 2025)
This study explores the phenomenon of language change in the communication patterns of Generation Z, a demographic cohort born between the mid-1990s and early 2010s, known for their deep integration with digital technology and social media. The research investigates how linguistic shifts—such as the emergence of new slang, abbreviations, code-switching, and emotive expressions—reflect the values, identity, and communication preferences of this generation. Utilizing a qualitative-descriptive approach, the data was collected through observations of online conversations, social media interactions, and informal interviews with Gen Z participants. The findings reveal that language change among Gen Z is significantly influenced by digital platforms such as TikTok, Instagram, and messaging apps, where brevity, creativity, and speed of communication are prioritized. Additionally, the blending of English with native languages, frequent use of memes, emojis, and internet-born expressions are indicative of their unique linguistic landscape. These changes not only reflect evolving communication norms but also challenge traditional views of grammar, vocabulary, and language usage. The study highlights the need for educators and linguists to acknowledge and adapt to these changes in order to remain relevant and effective in language teaching and sociolinguistic analysis.